Transformer-Less Cascaded Voltage Source Converter Based STATCOM - Rashmi Sharma; Vijay H Makwana (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2022)
In this work, a transformer-less voltage source converter (VSC) based STATCOM is proposed with a combination of cascaded conventional three-phase voltage source inverters. This modular structure provides multilevel operation with reduced switch count and independent DC-link capacitors. The actual contribution of this paper is the transformer-less configuration of a conventional cascaded voltage source converter which provides reduced cost and volume as compared to other transformer-less converter configurations. The system provides reactive power compensation with better power quality when connected to the nonlinear power electronics load also. A simple control system is provided for balancing the Dc link capacitor voltage and reactive power compensation. The validation of the proposed model is analyzed with simulation using MATLAB/SIMULINK software and the results are obtained with different linear and nonlinear load configurations.